2021
DOI: 10.1038/s41598-021-85303-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of age, sex, and joint form on degenerative lesions of the sacroiliac joints on CT in the normal population

Abstract: Degeneration of the sacroiliac joints (SIJs) is a common finding, while its underlying cause and development remain incompletely understood. The aim of this investigation was to describe the spatial distribution of degenerative SIJ changes across age groups and to investigate for the first time their relationship to anatomical form and sex. For this IRB-approved investigation, demographic data of 818 patients without SIJ disease were retrieved from electronic patient records. High-resolution computed tomograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 27 publications
4
35
1
1
Order By: Relevance
“…To date, the evidence base of the association of sacroiliac joint disease and joint form variation is still sparse. In a large study on more than 800 patients without SIJ-related symptoms, we found a significant association between joint sclerosis and accessory joint facets (OR 2.7) [ 22 ]—the observed sclerosis is typically found in the dorsal and caudal aspects of the joints, indicating a pathological bony contact (see Fig. 2 ).…”
Section: Joint Forms and Sij Diseasementioning
confidence: 94%
See 4 more Smart Citations
“…To date, the evidence base of the association of sacroiliac joint disease and joint form variation is still sparse. In a large study on more than 800 patients without SIJ-related symptoms, we found a significant association between joint sclerosis and accessory joint facets (OR 2.7) [ 22 ]—the observed sclerosis is typically found in the dorsal and caudal aspects of the joints, indicating a pathological bony contact (see Fig. 2 ).…”
Section: Joint Forms and Sij Diseasementioning
confidence: 94%
“…However, recent developments in imaging techniques such as dual-energy CT (for detection of bone marrow lesions) [31,32] or direct depiction of the bone in MRI, e.g., with synthetic CT [33], have the potential to improve the diagnostic workup. So far, classification of sacroiliac joint form in Images adapted with the authors' permission from [22] radiography has not been attempted. Therefore, a reliable detection and evaluation of the impact in an individual patient remains the domain of MRI and CT.…”
Section: Imaging Of Joint Formsmentioning
confidence: 99%
See 3 more Smart Citations